Kustannuserot maidon, sianlihan ja viljan tuotannossa - Mäkimattila, Mauri (Maatalouden taloudellinen tutkimuslaitos, 1998)
Kirjanpitotiloilta tehdyn selvityksen mukaan maatalouden tuotantokustannukset vaihtelevat merkittävässä määrin tilojen välillä. Jaettaessa maitotilat kustannusten mukaan kolmeen yhtä suureen ryhmään maitolitran tuotantokustannus oli alimpien kustannusten tilaryhmässä 2,50 mk, mutta korkeimpien kustannusten ryhmässä yli puolet enemmän. Myös sianlihan tuotannossa korkeimpien kustannusten tilakolmanneksessa tuotantokustannus oli puolet suurempi kuin alimpien kustannusten ryhmässä. Viljatiloilla tuotantokustannus oli korkeimpien kustannusten tilaryhmässä lähes kaksinkertainen alimpien kustannusten tilakolmannekseen verrattuna. Tuotantokustannukseen on luettu kaikki tuotteen tuottamisesta aiheutuvat kustannukset mukaan lukien viljelijäperheen laskennallinen palkkavaatimus (40 mk/tunti) ja oman pääoman korkovaatimus (5%) sekä velkojen korot. TUOTANTO- KUSTANNUS Alimpien kustannusten tilakolmannes Keskimäärin Korkeimpien kustannusten tilakolmannes Maitotilat, mk/l 2,50 3,09 3,78 Lihasikatilat, mk/kg 11,31 13,69 16,99 Viljatilat, mk/kg 1,10 1,53 2,03 Osa tilojen välisistä tuotantokustannusten eroista johtuu tilakokoeroista, mutta myös saman kokoisilla tiloilla tuotantokustannuksissa oli eroja. Saman suuruisen vuosituotoksen aikaansaamiseen tarvittavat kustannukset vaihtelivat maitotiloilla enimmillään noin 1,50 mk/l, lihasikatiloilla lähes neljä markkaa kilo ja viljatiloilla yli markan kilo. Koska osalla tiloista tuotantokustannukset on onnistuttu pitämään kohtuullisella tasolla, keinot kustannusten alentamiseen ovat olemassa. Vaikka maatalouden kustannuksia on viime vuosina voimakkaasti karsittu, osalla tiloista kannattavuutta voidaan edelleen parantaa tarkalla talouden pidolla.

In this study the production costs of milk, cereals and pigmeat are examined on the basis of the results from the bookkeeping farms in 1996. Farms have been classified on the basis of the production cost. The production costs have also been calculated for the different support areas, and they have been compared to the production costs prior to the EU membership. The average production cost for milk was FIM 3.09/l. On about a one third of the farms the production cost for milk was less than FIM 2.75/l, and on about half of the farms it was below FIM 3.00/l in 1996. When the farms were classified into four groups of an equal size on the basis of the profitability coefficient, the production cost in the best group was FIM 2.51/l and in the worst it was FIM 3.78/l. The best and the worst groups differed in the first place in terms of the labour cost and depreciations. According to the support areas, the production cost was the lowest in area C1 and the highest in area C4. The average production cost for milk fell by 22% between 1992 and 1996 and by 16% from the year 1995. The average production cost for cereals was FIM 1.53/kg. On 23% of the farms the production cost of cereals was below FIM 1.20/kg, and on 64% of the farms the cost was less than FIM 1.60/kg. When the farms were divided into the four profitability classes, on farms with the highest profitability the production cost was FIM 1.14/kg and in the group with the lowest profitability it was FIM 1.91/kg. The differences were the greatest in the labour cost and depreciations. In terms of the support areas the production cost was the highest in area A and the lowest in area C. The average production cost for cereals have fallen by 37% between 1991 and 1996 and by 23% from the year 1995. The average production cost for pigmeat was FIM 13.69/kg. 9% of the pig farms produced a kilo of pigmeat for less than FIM 11.00, and on 52% of the farms the cost was below FIM 13.00. When the pig farms were divided into three profitability classes, in the one third with the highest profitability the production cost was FIM 11.21/kg, and in the weakest third it was FIM 16.28/kg. When examined according to the support area, the production cost was the lowest in area C and the highest in area A, in which the labour cost and depreciations were clearly higher than in the other areas. The production costs of pigmeat decreased by the average of 31% between 1992 and 1996, but only by 3 % from the previo
Production costs of milk, cereal and pigmeat
Keywords: Ma; tuotantokustannukset; kirjanpitotilat; kannattavuus; production costs; profitability; bookkeeping farms